2019
DOI: 10.3390/met9111173
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Chalcopyrite Leaching by Hydrogen Peroxide in Sulfuric Acid

Abstract: In ores, chalcopyrite is usually associated with other sulfide minerals, such as sphalerite, galena, and pyrite, in a dispersed form, with complex mineralogical structures. Concentrates obtained by flotation of such ores are unsuitable for pyrometallurgical processing owing to their poor quality and low metal recovery. This paper presents the leaching of chalcopyrite concentrate from the location “Rudnik, Serbia”. The samples from the flotation plant were treated with hydrogen peroxide in sulfuric acid. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 58 publications
1
31
0
1
Order By: Relevance
“…In research on the leaching of bornite done by Pesic and Olson [20], the dissolution of copper from bornite reached 26 to 28% during the first hour of the process in the presence of ferric ion, which are values greater than those obtained in this study in a chloride medium and without the initial presence of ferric ion, as shown in Figure 1. Furthermore, in the studied system, this function can be performed by the Cu 2+ /Cu + redox pair, which was formed from dissolved soluble copper [35], but it is restricted because the leaching systems require the addition of oxygen for the oxidation of the cuprous products [7,36], according to Reactions (4) and (5).…”
Section: Leaching Without Pre-treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In research on the leaching of bornite done by Pesic and Olson [20], the dissolution of copper from bornite reached 26 to 28% during the first hour of the process in the presence of ferric ion, which are values greater than those obtained in this study in a chloride medium and without the initial presence of ferric ion, as shown in Figure 1. Furthermore, in the studied system, this function can be performed by the Cu 2+ /Cu + redox pair, which was formed from dissolved soluble copper [35], but it is restricted because the leaching systems require the addition of oxygen for the oxidation of the cuprous products [7,36], according to Reactions (4) and (5).…”
Section: Leaching Without Pre-treatmentmentioning
confidence: 99%
“…Traditionally, froth flotation and pyrometallurgical processes have been used for the treatment of copper concentrates from high-grade copper ores [2,3]. However, the constant decrease in ore grade, presence of toxic elements, and stricter environmental legislations make the hydrometallurgical option way more attractive [4,5]. In the last years, research and development have intensified in the search for hydrometallurgical alternatives to the processing of copper concentrates [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Značajan deo bakra u zemljinoj kori nalazi se u obliku halkopirita. On je u polimetaličnim rudama često srastao i pojavljuje se sa drugim sulfidnim mineralima, poput pirita, galenita i sfalerita i mineralima jalovine [1,2]. Pored toga, opšta karakteristika većine eksploatisanih sulfidnih ležišta ogleda se u minerološkoj segregaciji, gde se u površinskim slojevima ležišta koncentriše oksidna ruda, u srednjim slojevima oksidno-sulfidna i konačno u dubljim slojevima ležišta sulfidna ruda.…”
Section: Uvodunclassified
“…Froth flotation produces copper concentrate with some trace elements that are considered impurities, principally arsenic and antimony, and minor elements such as Cd, Hg, Pb, Bi, Se, and Te. The most common mineralogical species associated with toxic impurities present in copper concentrates are enargite (Cu 3 AsS 4 ), arsenopyrite (FeAsS), rejalgar (AsS), tennantite (Cu 12 As 4 S 13 ), tetrahedrite (Cu 12 Sb 14 S 13 ), and famatinite (Cu 3 SbS 4 ) [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%